The antithrombin binding regions of heparin mediate fetal growth and reduced placental damage in the RUPP model of preeclampsia. Issue 5 (17th January 2020) - Wat, Jovian M; Baczyk, Dora; Kingdom, John C
Abstract: Preeclampsia is a serious hypertensive disorder of pregnancy, which is only cured with delivery of the placenta, thereby commonly necessitating preterm birth of the fetus. Low-molecular-weight heparin (LMWH) has demonstrated potential to reduce the incidence of preeclampsia in high-risk pregnant women, although the underlying mechanism by which LMWH protects against preeclampsia is unknown. Given the complex structure and biologic actions of heparin, we tested the hypothesis that heparin can mediate preeclampsia prevention via nonanticoagulant pathways. We compared the effects of a nonanticoagulant, glycol-split LMWH (gsHep)—rendered nonanticoagulant through disruption of the antithrombin binding regions—with the LMWH dalteparin in the rat reduced uterine perfusion pressure (RUPP) surgical model of preeclampsia. Although RUPP animals exhibit significantly elevated blood pressure and reduced plasma levels of placental growth factor (PGF) compared to sham, neither dalteparin nor gsHep treatment significantly impacted these parameters. However, the observed positive correlation between PGF levels and number of viable fetuses in RUPP-induced animals suggests that reduced PGF levels were predominately due to placental loss. Daily subcutaneous injections of low-dose dalteparin but not gsHep significantly restored fetal growth that was impaired by RUPP surgery. Placentas from RUPP animals exhibited an abnormal labyrinth structure, characterized by expanded sinusoidal blood spaces, relative to sham-operated animals. Morphometric analysis demonstrated that dalteparin but not gsHep treatment normalized development of the labyrinth in RUPP-exposed conceptuses. These data suggest that the antithrombin-binding regions of LMWH are required to confer its protective effects on fetal growth and placental development. Abstract : Low-molecular-weight heparin promotes placental development and fetal growth, thereby providing a mechanism by which heparin therapy could benefit pregnant women at risk of preeclampsia with growth restricted fetuses.